Refleksi Tradisi Orang Rimba dalam Dongeng Bujang Kelingking dan Anak Dewa Padi: Perspektif Sosiologis - Yusanti, Elva (METASASTRA: Jurnal Penelitian Sastra, 2018)
The tradition of a society can be reflected into their literary works. Similarly, the tradition of Orang Rimba is also reflected in the folktales of “Bujang Kelingking” and “Anak Dewa Padi”. The problem of this study is how the traditions of Orang Rimba are reflected in both folktales. This study aims at describing the traditions of Orang Rimba portrayed in those folktales. The research uses a sociological perspective which correlates text with social context of Orang Rimba. This study applies qualitative methods with an annotated bibliography and interview techniques. The result of this study shows that the traditions of Orang Rimba contained in the folktales are the traditions of settling, hunting, and farming. Furthermore, the traditions related to the kinship and belief systems are mirrored in those folktales as well.